Trends and prospects for the development of Ecuadorian-Peruvian relations - V. X. Medina González; E. Orellana Solano (Ибероамериканские тетради, 2022)
The article examines key trends and prospects for the development of Ecuadorian-Peruvian relations, which are of particular interest in the sphere of international cooperation for both Ecuador and Peru. The purpose is to examine the trends of cooperation in various areas between Peru and Ecuador. In accordance with the main goal, the following objectives were set: to identify the features of joint coordination of stability in the border areas, including activities to curb illegal trade of weapons and drugs; to examine Ecuadorian-Peruvian economic relations, including development of trade relations; to identify key aspects of the development of Ecuadorian-Peruvian relations in culture, education and tourism, as well as environmental cooperation and support for indigenous peoples. In the areas of culture, tourism, education and the environment, Ecuadorian-Peruvian relations are quite underdeveloped and require activation of a number of measures proposed by the authors: improvement of the legal and regulatory framework in the field of above mentioned relations; increased financial support for cooperation in culture, education, tourism and the environment; increased promotion of the importance of relations between Ecuador and Peru, especially among youth; attraction to more active cooperation of public representatives organizations and businesses. Another important factor is the enhanced activity of Ecuadorian representatives in attracting foreign direct investment from Peru for the implementation of projects in different sectors of the economy in the country.